2020
DOI: 10.1002/app.49423
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of partially hydrolyzed polyacrylamide/polyethyleneimine reinforced with coal fly ash for preformed particle hydrogels

Abstract: High water production and low oil recovery are attributable to reservoir heterogeneity, making extraction economically inefficient. To improve oil production, it is important to solve permeability issues, to allow a more uniform and efficient sweep. In recent years, several studies of preformed particle gel (PPG) have been performed reduce reservoir heterogeneity and enhance oil recovery. In this work, the effect of coal fly ash (CFA) on hydrolyzed polyacrylamide (PHPA) crosslinked with polyethyleneimine PPG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This is an intrinsic characteristic of biopolymers whose polymer chains have high mechanical strength when subjected to high frequencies, 7 which is not observed in synthetic polymers 32,33 . At lower frequencies, rupture of the material's microstructure (rupture of the intermolecular forces between the chains) can be observed, and thus a decline in the elastic modulus and increase of the viscous modulus.…”
Section: Resultsmentioning
confidence: 97%
“…This is an intrinsic characteristic of biopolymers whose polymer chains have high mechanical strength when subjected to high frequencies, 7 which is not observed in synthetic polymers 32,33 . At lower frequencies, rupture of the material's microstructure (rupture of the intermolecular forces between the chains) can be observed, and thus a decline in the elastic modulus and increase of the viscous modulus.…”
Section: Resultsmentioning
confidence: 97%
“…The gelling solutions are placed in sealed bottles so that the total volume of the system is equal to half the volume of the bottle. The gel consistency is determined by inverting the bottles and observing the characteristics of the system under the effect of gravity, ranked by an alphabetic code from A to J, where: (A) means no detectable gel formed; (B) denotes highly flowing gel; (C) means flowing gel; (D) is moderately flowing gel; (E) denotes barely flowing gel; (F) pertains to highly deformable nonflowing gel; (G) mean moderately deformable nonflowing gel; (H) denotes slightly deformable nonflowing gel; (I) means rigid gel; and (J) denotes highly rigid gel 31,36 …”
Section: Experimental Partmentioning
confidence: 99%
“…Among the reinforcing fillers used to formulate these hydrogels are substances with a structure based on metallic oxides or modified bentonite clay. Studies have shown that the respective properties are closely related to improving the performance of hydrogels 15,27–33 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, research is being conducted on the creation of gels using preformed particles (PPG) that can eliminate reservoir heterogeneity and increase oil recovery. In a study conducted by K. Pereira et al [34], the influence of coal fly ash (CFA) on hydrolyzed polyacrylamide (PHPA), cross-linked using polyethylenimine (PPG), was investigated to analyze changes in their thermal, rheological, and structural properties.…”
Section: The Application Of Fly Ash In Various Areas Of the Oil And G...mentioning
confidence: 99%